Foreign Language Writing Anxiety: The Perceptions and Experiences of Freshmen Lebanese University Students - LABABIDI, ROLA (Advances in Social Sciences Research Journal, 2021)
Writing is an essential skill for language production. However, many English as Foreign language learners (EFL) face many difficulties in writing. This study aims to shed light on the psychological aspect of writing; more specifically writing anxiety. Consequently, the main purpose of this exploratory mixed-method study is to explore and investigate the sources and manifestations of foreign language writing anxiety among Lebanese university students. The participants were Lebanese EFL university students (N=87). Data for this study was gathered from the use of the Second Language Writing anxiety scale(SLWAI), Sources of Writing Anxiety Inventory(SWAI), and semi-structured Focus group interviews (FG). Focus interviews with students were used to triangulate the derived data from the inventories. This study provides numerical data regarding the level of writing anxiety among students. The data from the FG interviews were transcribed and uploaded for thematic coding and further analysis. The results from this study shed light on the sources and manifestation of the writing anxiety among students. It also helps to disseminate several practical recommendations for the alleviation of writing anxiety among students. It is assumed that the findings will address the perceived psychological needs of Lebanese EFL learners and provide grounds for further research.